Total Elbow Arthroplasty in Obese Patients - Yaser M. K. Baghdadi; Christian Veillette; Alex A. Malone; B.F. Morrey; Joaquín Sánchez‐Sotelo (2014)
Background: The prevalence of obesity in the United States has increased in recent decades. The aim of this study was to evaluate the influence of obesity in patients undergoing primary total elbow arthroplasty. Methods: From 1987 to 2006, 723 primary semiconstrained, linked total elbow arthroplasties were performed in 654 patients. The average patient age (and standard deviation) at the time of surgery was 62.3 ± 13.7 years, with 550 total elbow arthroplasties (76%) performed in women. Total elbow arthroplasties were used to treat inflammatory conditions in patients undergoing 378 total elbow arthroplasties (52%) and to treat acute traumatic or posttraumatic conditions in patients undergoing 310 total elbow arthroplasties (43%). Patients were classified as non-obese (having a body mass index of <30 kg/m2) in 564 total elbow arthroplasties (78%) and as obese (having a body mass index of ≥30 kg/m2) in 159 total elbow arthroplasties (22%). The median duration of follow-up was 5.8 years (range, zero to twenty-five years). Survivorship of total elbow arthroplasty was estimated with use of the Kaplan-Meier method. The effect of obesity on risk of total elbow arthroplasty revision was estimated with use of Cox regression models, adjusting for age, sex, body mass index, and indication. Results: A total of 118 revisions (16%) were performed. The ten-year survival rate for total elbow arthroplasty revision for any reason was 86% (95% confidence interval, 82% to 89%) in non-obese patients compared with 70% (95% confidence interval, 60% to 79%) in obese patients (p < 0.05). The ten-year survival rate for total elbow arthroplasty revision for mechanical failure was 88% (95% confidence interval, 84% to 91%) in non-obese patients compared with 72% (95% confidence interval, 61% to 81%) in obese patients (p < 0.05). Severely obese patients (those with a body mass index of 35 to <40 kg/m2) had a significantly higher risk of total elbow arthroplasty revision for any reason (hazard ratio, 3.08 [95% confidence interval, 1.61 to 5.45]; p < 0.05) and mechanical failure (hazard ratio, 3.10 [95% confidence interval, 1.47 to 5.89]; p < 0.05) compared with non-obese patients. Conclusions: Obesity adversely influences the performance of elbow replacement after primary total elbow arthroplasty. Obese patients being considered for elbow replacement surgery should be counseled accordingly. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.